Mobility and land use in the Greater Khorasan Civilization: Isotopic approaches (87Sr/86Sr, δ18O) on human populations from southern Central Asia. (December 2022) - Kroll, Sonja; Bendezu-Sarmiento, Julio; Lhuillier, Johanna; Luneau, Élise; Kaniuth, Kai; Teufer, Mike; Mustafakulov, Samariddin; Khasanov, Mutalib; Vinogradova, Natalia; Avanesova, Nona; Fiorillo, Denis; Tengberg, Margareta; et al.
Highlights: Collection of a biogeochemical dataset of 87 Sr/ 86 Sr isotopes from southern Central Asia. Mobility according to 87 Sr/ 86 Sr and δ 18 O isotopes in the Greater Khorasan Civilization. Interregional migration and individual resettlements of Bronze Age human populations. Long distance contacts between Bronze Age steppe communities. Variable land use during the Bronze Age in Turkmenistan, Uzbekistan, Tajikistan. Abstract: The question of mobility of Bronze Age societies in southern Central Asia is a lively subject for discussion and remains a key aspect for understanding past human life. Central Asia represents a region where mobility and migration had a deep impact on the development of cultural communities. Surrounded by the great empires of the ancient Near East, it exhibited a high ethnic and genetic diversity. In this paper we present a regional study for southern Central Asia of isotopic analyses of 87 Sr/ 86 Sr and δ 18 O of human samples from several Bronze Age sites in southern Turkmenistan (Ulug Depe), south/central Uzbekistan (Dzharkutan, Sapallitepa, Tilla Bulak, Bustan and Bashman 1) and southern Tajikistan (Saridzhar, Gelot and Darnaichi). The three geographical zones manifest different patterns of mobility. The analysis of the Ulug Depe people demonstrates a high rate of immigration during the early periods (EBA) and a tendency for permanent residence. The later periods (MBA) are marked by a decrease in immigration and mobility, indicating a more extensive use of the surrounding landscape. Dzharkutan people displayed a different and complex pattern of mobility and subsistence, with frequent movements during individual lifetime within a limited area. The other sites in the Surkhan Darya Valley and southern Tajikistan indicate active mobility in which individuals migrated within a wide area of southern Central Asia.